2017
DOI: 10.1177/1747493017711813
|View full text |Cite
|
Sign up to set email alerts
|

Standardized measurement of sensorimotor recovery in stroke trials: Consensus-based core recommendations from the Stroke Recovery and Rehabilitation Roundtable

Abstract: Kwakkel, G. et al. (2017) Standardized measurement of sensorimotor recovery in stroke trials: consensus-based core recommendations from the Stroke Recovery and Rehabilitation Roundtable. International Journal of Stroke, 12(5), pp. 451-461. (doi:10.1177/1747493017711813) This is the author's final accepted version.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/144577/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
394
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 390 publications
(422 citation statements)
references
References 54 publications
5
394
0
6
Order By: Relevance
“…Yet, there were high attrition rates and bias, and variable outcomes used, which prevented metaanalysis. These issues are not isolated to RPD; the Stroke Recovery and Rehabilitation Roundtable group highlighted this as common in stroke rehabilitation trials (10,65,66). Nevertheless, several classes of RPDs should be discussed in more detail.…”
Section: Eighteen Of 28 Drug Interventions Identified In Thismentioning
confidence: 99%
“…Yet, there were high attrition rates and bias, and variable outcomes used, which prevented metaanalysis. These issues are not isolated to RPD; the Stroke Recovery and Rehabilitation Roundtable group highlighted this as common in stroke rehabilitation trials (10,65,66). Nevertheless, several classes of RPDs should be discussed in more detail.…”
Section: Eighteen Of 28 Drug Interventions Identified In Thismentioning
confidence: 99%
“…Apart from its popularity, the robust and sensitive nature of the ARAT are indicated by its use as a criterion measure in validation studies for new, existing and/or modified assessments Blennerhassett, Avery & Carey, 2010;Edwards, Lang, Wagner, Birkenmeier & Dromerick, 2012;Page, Hade & Persch, 2015). The ARAT has also been included in clinical practice guidelines and consensus statements relevant to neurorehabilitation, stroke (Kwakkel et al, 2017;Sullivan et al, 2013) and upper limb spasticity (Sheean, Lannin, Turner-Stokes, Rawicki & Snow, 2010).…”
Section: Arat Uptakementioning
confidence: 99%
“…These movements are needed to perform many everyday tasks. For this reason, an inability to perform test items is thus proposed to be a valid indicator of upper limb activity limitation (Kwakkel et al, 2017). The ARAT has been demonstrated to be unidimensional, measuring the single construct of upper limb function related to everyday activities (Koh et al, 2006;Van der Lee, Roorda, Beckerman, Lankhorst & Bouter, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For every stroke recovery trial, the following assessments are recommended: NIHSS to characterize baseline stroke severity, Fugl-Meyer Assessment to characterize impairment, Action Research Arm Test to characterize activity limitation, a 10-meter walk test, a self-reported questionnaire of health status (EQ-5D) for quality of life, and the modified Rankin Scale to characterize global disability. 80 If possible, kinematic and kinetic information should also be collected, which can tease apart the contribution of true motor recovery versus compensation. Some questions to think about in the context of MST include: What ICF domains does it target?, and What aspects of movement are being retrained and therefore are expected to change?…”
Section: How Do We Move Forward?mentioning
confidence: 99%